An integrated 2‐bit metasurface array antenna with broadband low radar cross‐section covering large incident angle space. Issue 6 (4th April 2022) - Zhang, Zhiyun; Liu, Tao; Cao, Xiangyu; Yang, Huanhuan; Jidi, Liaori; Gao, Jun
Abstract: Based on an integrated design of metasurface units and antenna elements, a 2‐bit metasurface array antenna with broadband low radar cross‐section (RCS) covering large incident angle space is proposed in this study. The slot width's influences on the reflective phase and element radiation performance are analysed. Furthermore, a genetic algorithm is utilised to obtain the coding pattern of the array antenna with diffuse scattering characteristics. A wideband RCS reduction is achieved from 4.2 to 9.0 GHz under x‐polarised incidence, and it has oblique incident angle stability ranging from 0° to 60° due to non‐uniform element arrangement. The current cancelation phenomenon is found to reveal the RCS reduction mechanism. Besides, the proposed antenna gain is 15.9 dBi with a peak aperture efficiency of up to 90.8%. Experimental results have a close coincidence with the simulations, which verifies the capability of the proposed design.